Feminist Stylistic Analysis of Bella Poarch's Song "Build A Bitch" - Tarigan, Aina Zahra; Tambunan, Cindy Uli Basa; Mentari, Lanjar Melati Setio; Rangkuti, Rahmadsyah (Linguistics and ELT Journal, 2023)
This research aims to examine Bella Poarch's song "Build a Bitch" from a feminist stylistic point of view. This research is conducted using Sara Mills' feminist stylistics theory which consists of three levels as suggested by Mills in her book. The analysis is conducted using descriptive-qualitative methodology that involves collecting and analyzing data at the word level, analyzing at the phrase/sentence level, and analyzing at the discourse level, and relating it to gender issues. The findings show an advanced representation of traditional gender roles, specifically the narrative's objectification of women. The metaphorical employing of the phrases 'Barbie' and 'Ken' exposes gender biases along with judging social beauty standards and unacceptable gender roles assigned to women. The song arises as a critique of traditional gender norms, combining with feminist stylistic elements by questioning and disputing society demands on women. The song navigates relationships complexities and society expectations critically, providing the speaker to stand against standards and fight for self-love.